Effect of Three Different Remineralizing Agents on White Spot Lesions; AnIn Vitro Comparative Study - Soodeh Tahmasbi; Mahya Adhami; Azam Valian; Roya Hamedi (Journal of Islamic Dental Association of Iran, 2016)
Background and Aim: White spot lesions (WSLs) are common occurrence following orthodontic treatment, this study sought to compare the remineralizing potential of fluoride, MI Paste Plus (CPP-ACP-F) and Remin Pro for treatment of WSLs.